2009
DOI: 10.1111/j.1365-2621.2007.01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Betalains: properties, sources, applications, and stability – a review

Abstract: Consumers are increasingly avoiding foods containing synthetic colourants, which lead food industries to replace them by natural pigments, such as carotenoids, betalains, anthocyanins and carminic acid. Betalains are water-soluble nitrogen-containing pigments, composed of two structural groups: the red-violet betacyanins and the yellow-orange betaxanthins. This review synthesises the published literature on basic chemistry of betalains, their sources and chemical stability. Moreover, several works are mentione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
457
0
44

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 587 publications
(517 citation statements)
references
References 128 publications
(314 reference statements)
16
457
0
44
Order By: Relevance
“…The hierarchical order observed agrees with the data found by other researchers, were the amount of betalains increased from yellow to red and to purple varieties (Farag et al, 2017). Several works have demonstrated the antiradical scavenging activity of betalains in vitro (Azeredo, 2009), which can contribute to the prevention of several degenerative diseases. Therefore, betalains could be a great substitutive of artificial dyes with additional bioactive activity.…”
Section: Hydrophilic and Lipophilic Compoundssupporting
confidence: 81%
See 2 more Smart Citations
“…The hierarchical order observed agrees with the data found by other researchers, were the amount of betalains increased from yellow to red and to purple varieties (Farag et al, 2017). Several works have demonstrated the antiradical scavenging activity of betalains in vitro (Azeredo, 2009), which can contribute to the prevention of several degenerative diseases. Therefore, betalains could be a great substitutive of artificial dyes with additional bioactive activity.…”
Section: Hydrophilic and Lipophilic Compoundssupporting
confidence: 81%
“…gialla and sanguigna do not show significant differences in most of the macronutrients, excluding proteins and ash content. Higher percentages in proteins could be due to a greater concentration of pigments in the cell vacuoles, betalainic colorants being water-soluble nitrogen-containing pigments (Azeredo, 2009), Table 1 Morphological parameters of Opuntia spp.…”
Section: Morphological Parameters and Nutritional Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shrinkage reached its peak at 10 days in storage and changed only slightly with additional storage time. This lower value could be due to the following: (1) the betalains reacted with the sausages' free radicals produced by lipid oxidation, (2) the betalains migrated from the film to the sausage and/or (3) betalains were exposed to light and air (Azeredo, 2009). In order for betalains to have a beneficial effect on the human body, it is recommended that the food contain ≈39 µg/g (Kanner, Harel, & Granit, 2001).…”
Section: Betalain Quantificationmentioning
confidence: 99%
“…These pigments are mainly found in the vacuoles of all their tissues 1 . Betalains confer these plants their yellow, orange, red and violet colours 2 and are powerful antioxidants 3,4 . In the course of evaluating the antioxidant properties of betanidin 2 , the aglycone of the most common betalain, in the pathophysiology of atherosclerosis, we found that betanidin has an effect in the blood glucose levels in BALB/c mice fed with an atherogenic diet.…”
Section: Introductionmentioning
confidence: 99%